1997
DOI: 10.1038/sj.bjp.0700946
|View full text |Cite
|
Sign up to set email alerts
|

Aminoguanidine‐effects on endoneurial vasoactive nitric oxide and on motor nerve conduction velocity in control and streptozotocin‐diabetic rats

Abstract: 1 The e ects of aminoguanidine (AG) treatment on reductions in motor nerve conduction velocity (MNCV) and sciatic nerve blood¯ow, indexed by laser Doppler¯ux (LDF), were investigated in rats with experimental diabetes (streptozotocin-induced; 8 ± 10 weeks duration). The contribution of endoneurial vasoactive nitric oxide to the LDF of these animals was also investigated by the direct micro-injection of N G -nitro-L-arginine methyl ester (L-NAME; 1 nmol in 1 ml), followed by L-arginine (100 nmol in 1 ml), into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
(63 reference statements)
3
12
1
Order By: Relevance
“…As has been previously reported, we demonstrate that treating streptozotocin-induced diabetic rats with sorbinil or aminoguanidine significantly improves the reduction in EBF and slowing of MNCV [3][4][5][6][7][8][9][10][11][12][24][25][26][27][28]. In sorbinil treated diabetic rats EBF and MNCV remained suppressed by 15 and 18%, respectively compared to controls, whereas in aminoguanidine treated rats EBF and MNCV, compared to controls, was decreased by 6 and 16%, respectively.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…As has been previously reported, we demonstrate that treating streptozotocin-induced diabetic rats with sorbinil or aminoguanidine significantly improves the reduction in EBF and slowing of MNCV [3][4][5][6][7][8][9][10][11][12][24][25][26][27][28]. In sorbinil treated diabetic rats EBF and MNCV remained suppressed by 15 and 18%, respectively compared to controls, whereas in aminoguanidine treated rats EBF and MNCV, compared to controls, was decreased by 6 and 16%, respectively.…”
Section: Discussionsupporting
confidence: 57%
“…We have previously shown that endothelialdependent vascular relaxation of arterioles that provide circulation to the region of the sciatic nerve is impaired by diabetes [35,36]. In the present study we sought to determine the effect treatment of diabetic rats with sorbinil, an aldose reductase inhibitor, aminoguanidine, an inhibitor of nonenzymatic glycation, or myoinositol supplementation has on EBF, MNCV as well as vascular relaxation of arterioles that provide circulation to the region of the sciatic nerve.As has been previously reported, we demonstrate that treating streptozotocin-induced diabetic rats with sorbinil or aminoguanidine significantly improves the reduction in EBF and slowing of MNCV [3][4][5][6][7][8][9][10][11][12][24][25][26][27][28]. In sorbinil treated diabetic rats EBF and MNCV remained suppressed by 15 and 18%, respectively compared to controls, whereas in aminoguanidine treated rats EBF and MNCV, compared to controls, was decreased by 6 and 16%, respectively.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…Its effects on nerve morphometry have not been assessed at this stage because aminoguanidine treated animals have not reached the duration of diabetes for nerve biopsies electrophysiological results lead us, however, to believe that aminoguanidine will have little it any effect on structural changes. The inability of aminoguanidine to restore nerve function in baboons differs from some of the studies in rats that showed treatment to be beneficial although the results are conflicting [18,19,22,41,42]. One study found that diabetic rats given 50 mg/kg aminoguanidine in the drinking water for 16 weeks had NCV restored although doses of 10 and 25 mg/ kg were ineffective [19].…”
Section: Discussionmentioning
confidence: 74%